The European Medical Device Regulation–What Biomedical Engineers Need to Know - Tom Melvin (IEEE Journal of Translational Engineering in Health and Medicine, 2022)
The Medical Device Regulation (EU) 745/2017 (MDR) has replaced the medical device directives which were in place since the early 1990s. MDR introduces a number of changes of relevance to biomedical engineers who work in healthcare institutions or with medical devices. This includes changes relating to devices produced in healthcare institutions, custom-made devices, single use devices, devices without an intended medical purpose, clinical investigations and device traceability. There are also challenges in implementation of the MDR, with a shortage of available notified bodies needed to conduct conformity assessment, with a consequent risk of product unavailability. Understanding these changes is important as implementing new requirements in practice may require additional resources or the introduction of new processes or systems.